Penerapan Prinsip Customer Due Diligence Di PT. Bank Muamalat Indonesia Cabang Medan Balai Kota, Tbk Dalam Rangka Mencegah Tindak Pidana Pencucian Uang - Arief Rezana Dislan; Bismar Nasution; Utari Maharany Barus; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
Abstract. Banking financial institutions in particular are very vulnerable to the possibility to be used as a medium of money laundering and financing of terrorism. This is due to various factors such as financial transactions in the banking flows very fast and occur in large numbers, and their wide selection of financial transactions. Due to the function and role of the vulnerable banks would require the presence of the precautionary principle (prudent) in every activity of activities, one of which is the obligation of the application of the principle of Customer Due Diligence (CDD). Application of the principle of Customer Due Diligence is one way to combat and prevent crime-related forms of money in banks in Indonesia. The method used is a kind of normative legal research methods. This legal research will examine the legal system that aims to discover the rules of law in the field of money laundering that could provide an explanation for the application of the principle of Customer Due Diligence (CDD) in order to prevent money laundering. Source of data used: secondary data includes primary legal materials, secondary legal materials, tertiary legal materials, and also uses primary data: data collection techniques with library research to obtain secondary data, in the form of primary legal materials, secondary and tertiary legal materials. This study also uses field research is to obtain primary data that interview. The problems discussed in this research is about the application of the principle of Customer Due Diligence (CDD), the type of laundering money in the bank, and the application of the principle of Customer Due Diligence (CDD) at PT. Bank Muamalat Indonesia, Tbk in preventing money laundering. Based on the results of the study indicate that CDD provided for in Article 1 PBI / 11/28/2009 on the Implementation of Anti-Money Laundering and Combating the Financing of Terrorism for Commercial Bank which is the application of the standard recommendations of the FATF (Financial Action Task Force). There are three stages in the process of money laundering in the banking ie Placement, Layering, and Integration. Application of CDD in PT. Bank Muamalat Indonesia, Tbk contained in the internal regulations "Procedures Implementation of the Anti-Money Laundering and Combating the Financing of Terrorism" performed at the stage of acceptance and customer identification, request for information, requests for documents, verification of documents, EDD (Enhanched Due Diligence), up to the updating of the customer in accordance with FATF recommendations and legislation, especially Law No. 8 of 2010 on Money Laundering and Bank Indonesia Regulation No. PBI / 11/28/2009 on the Implementation of Anti-Money Laundering and Combating the Financing of Terrorism for Commercial Banks. Application of Customer Due Diligence (CDD) must be improved. Banks must be able to identify customers and also know the transactions conducted by customers, so as to prevent the laundering of money by utilizing the bank.   Keywords :   Customer Due Diligence, Money Laundering.